2016
DOI: 10.1016/j.joca.2016.01.987
|View full text |Cite
|
Sign up to set email alerts
|

Changes in knee joint load indices from before to 12 months after arthroscopic partial meniscectomy: a prospective cohort study

Abstract: A relative increase in indices of medial compartment loading was observed in the leg undergoing APM compared with the contra-lateral leg from before to 12 months after surgery. This increase may contribute to the elevated risk of knee OA in these patients. Randomized trials including a non-surgical control group are needed to determine if changes in joint loading following APM are caused by surgery or by changes in symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
4
49
1
Order By: Relevance
“…5,16,52 However, meniscal tissue resection leads to altered knee joint loading, which increases the contact pressure on the remaining tissues in the joint. 4,51 Therefore, meniscectomy might increase the risk of subsequent cartilage injuries. 10,37,39,40 The indication for surgery might be a potential confounding factor 40 because underlying degenerative joint disease increases the risk of future cartilage degradation.…”
Section: Discussionmentioning
confidence: 99%
“…5,16,52 However, meniscal tissue resection leads to altered knee joint loading, which increases the contact pressure on the remaining tissues in the joint. 4,51 Therefore, meniscectomy might increase the risk of subsequent cartilage injuries. 10,37,39,40 The indication for surgery might be a potential confounding factor 40 because underlying degenerative joint disease increases the risk of future cartilage degradation.…”
Section: Discussionmentioning
confidence: 99%
“…At 1-year follow-up of patients previously diagnosed with concurrent osteoarthritis and meniscus damage, 80.8% of knees that underwent partial meniscectomy demonstrated cartilage loss in the interval period compared with 37.4% of knees that had no meniscus surgery. 6 This disparity may be attributed to the increased knee joint load following a partial meniscectomy, as noted by Thorlund et al 8 Compared with partial meniscectomies, meniscus repairs focus on preserving as much meniscal tissue as possible to retain its biomechanical properties. Today, the inside-out repair technique is considered the gold standard for treatment due to its good clinical outcomes in addition to its versatility and use of smaller diameter needles.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although meniscectomies provide symptomatic relief, the loss of meniscus tissue increases knee joint load and significantly increases the longterm risk for osteoarthritis. 7,8 Thus, if possible, a meniscus repair should be performed to retain biomechanical function.…”
mentioning
confidence: 99%
“…[6,14] . Increasingly more studies have suggested [15][16][17] that meniscus injury or defect will lead to an increase in the incidence of osteoarthritis, and thus meniscal repair has received increasingly more attention. Among the repair methods of meniscus injury [18] , meniscal suture repair is the mainstream repair method at present, and includes three types of repair: outside-in repair, inside-out repair and all-inside repair.…”
Section: Discussionmentioning
confidence: 99%